Community development initiatives as part of a tourism resort's CSR strategy : examination of a high-end luxury resort in the Maldives - Wolf, Mona (Massey University, 2021)
The tourism industry has been promoted as a beacon of hope to help develop emerging countries and rural areas. This aligns well with the idea that the private sector can play a role in addressing the United Nations’ Sustainable Development Goals (SDGs) by being more directly involved in development. The most commonly used development tool for companies is corporate social responsibility (CSR) programmes. This study explores those CSR activities of a resort in the Maldives that are intended to bring about improvements to the overall well-being of the local population. Such projects can be termed ‘Corporate Community Development’ (CCD) (Banks et al., 2016). The aim was to investigate which CCD initiatives the resort is conducting and to what extent the local community is an active partner in the process. The focus hereby is weighted towards the point of view of the local population to counteract the overwhelming majority of CSR analyses from a business perspective. Primary data was collected through a grey literature analysis of reports and websites, as well as semi-structured interviews with resort and community representatives. Due to the Covid-19 pandemic, no international travel was possible, and the conversations were conducted using online communication tools. The data was coded and analysed using thematic analysis and then put into perspective applying the Development First approach (Hughes & Scheyvens, 2016) as a theoretical framework. The results of the study showed that the resort is highly committed to sustainable practices and socially responsible behaviour which is rooted deeply in their company philosophy. However, the results also aligned with the insights of previous studies that most tourism businesses focus primarily on sustainability in an ecological sense. Furthermore, the findings show that while both sides are content with the partnership, which both sides describe as equal, there is a need to improve the communication between the resort and communities and to establish more defined processes of reporting as well as monitoring and evaluation.
Keywords: 350805 Tourism resource appraisal